Zonal and Zoogeographic Characteristic of the Ant Fauna (Hymenoptera, Formicidae) of Ukraine - Radchenko, A.G. (Вестник зоологии, 2011)
One hundred fourty ant species belonging to 38 genera of 5 subfamilies are known to occur in Ukraine nowadays. All the species are attributed to 16 zoogeographic complexes that are grouped into three faunogenetic classes. Comparative zonal and zoogeographical analysis of the fauna of different geographical regions of Ukraine has revealed their essential heterogeneity. The ant fauna of the Forest-Steppe zone is not original. At the same time, it is not transitive between the faunae of the Forest and Steppe zones. Ant fauna of the Forest-Steppe is related to those not the Steppe but the Forests zones, and the Forest-Steppe can be included in the southern subzone of a Forest zone of t Europe. В Украине известно 140 видов муравьев из 38 родов 5 подсемейств. Выделены 16 зоогеографических комплексов, отнесенных к трем фауногенетическим классам. Сравнительный зональный и зоогеографический анализ фаун различных физико-географических регионов Украины выявил их существенную разнородность. Показано, что фауна муравьев Лесостепи не является самобытной. В то же время, она не является переходной между фаунами лесов и степной зоны. По происхождению мирмекофауна Лесостепи связана с таковой не степной, а лесных зон, и, на основании данных о распространении муравьев, Лесостепь может быть включена в состав южной подзоны лесной зоны Европы.